Sirru Taqdiimi Kalimati At-Taqwa ala Al-Ilmi Fii Surah Al-Baqarah (Dirasah Dalaliyyah Siyaaqiyah) - Rochmad Rochmad; A. Fadly Rahman Akbar; Intan Pratiwi Mustikasari; Rizal Nur Haqoni (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
Purpose The aim of this study is to reveal two important aspects: first, to uncover the secrets of the words